Decoherence in an interacting quantum field theory: Thermal case - Koksma, Jurjen F.; Prokopec, Tomislav; Schmidt, Michael G. (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We study the decoherence of a renormalized quantum field theoretical system. We consider our novel correlator approach to decoherence where entropy is generated by neglecting observationally inaccessible correlators. Using out-of-equilibrium field theory techniques at finite temperatures, we show that the Gaussian von Neumann entropy for a pure quantum state asymptotes to the interacting thermal entropy. The decoherence rate can be well described by the single particle decay rate in our model. Connecting to electroweak baryogenesis scenarios, we moreover study the effects on the entropy of a changing mass of the system field. Finally, we compare our correlator approach to existing approaches to decoherence in the simple quantum mechanical analogue of our field theoretical model. The entropy following from the perturbative master equation suffers from physically unacceptable secular growth.
Gesehen am 06.07.2022